Von der neoliberalen zur sozialistischen Gouvernementalität Anforderungen an eine Rifondazione der Linken - Bischoff, Joachim; Hüning, Hasko; Lieber, Christoph (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
While the European socialdemocratic parties cling to their illusion that they could combine a shareholder approach to global capitalism with social welfare for everybody they damage the trust and the political orientation of their former electors and members. The emerging left vacuum could be filled by various groups which criticise global capitalism. A transformational as well as civilising approach of criticising capitalism could be developed if the oppositional forces could agree on first strategic steps towards an utopia of socialistic governmentality, that is a socialistic way and aim of governmental rationality. With Foucault we must realize that this rationality can't be found in the one and only true marxist state theory, but has yet to be invented.